1999
DOI: 10.1021/jf9806311
|View full text |Cite
|
Sign up to set email alerts
|

Solution and Film Properties of Sodium Caseinate/Glycerol and Sodium Caseinate/Polyethylene Glycol Edible Coating Systems

Abstract: The aim of this study is to determine the effects of plasticizer hydrogen bonding capability and chain length on the molecular structure of sodium caseinate (NaCAS), in NaCAS/glycerol and NaCAS/polyethylene glycol 400 (PEG) systems. Both solution and film phases were investigated. Glycerol and PEG reduced the viscosity of aqueous NaCAS, with the latter having a greater effect. This was explained in terms of protein/plasticizer aggregate size and changes to the conformation of the caseinate chain. In the film p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 30 publications
3
49
1
1
Order By: Relevance
“…With a ratio of 4:1, slightly thinner (0.085 mm) NaCas/Gly films reportedly possessed TS ~ 17-27 MPa and D ~ 10.5% [29], also in normal conditions, which is more similar to the values obtained in this work.…”
Section: Open Testssupporting
confidence: 88%
“…With a ratio of 4:1, slightly thinner (0.085 mm) NaCas/Gly films reportedly possessed TS ~ 17-27 MPa and D ~ 10.5% [29], also in normal conditions, which is more similar to the values obtained in this work.…”
Section: Open Testssupporting
confidence: 88%
“…Gelatin possesses a relatively disorganized structure, but it can renature during the gelling and film-forming process, partially reacquiring the collagen triple helix structure, a protein with a high degree of organization (Achet and He, 1995). According to Siew et al (1999), the increase in chain organization likely optimizes molecular packing, resulting in films with desirable mechanical and barrier properties.…”
Section: Mechanical Properties Of Csg Film Cross-linked With Tgmentioning
confidence: 99%
“…The possible explanation for this phenomenon is as more amount of plasticizer is inserted into the protein matrix the protein -weaker plasticizer bonds replace protein bonds. This results in an increase in the intermolecular spacing (Siew et al, 1999). In PEG plasticized β-Lg films phenomenal increases in permeability at high plasticizer concentrations can be attributed to the loss of cohesiveness in the film network due to increase in the number of plasticizer -plasticizer associations Previous studies have shown that PEG is an excellent plasticizer of polymers.…”
Section: Matrix Mobility In Maltitol / β-Lg Filmsmentioning
confidence: 99%
“…The presence of certain diluents tends to relax the high-energy regions thereby allowing rearrangement of the polymer chains and resulting in densification of the glass. Siew et al (1999) reviewed that antiplasticization has been hypothesized to involve a combination of several factors. These include a possible reduction in free volume of the polymeric system, polymer-diluent interactions which create steric hindrance and decrease segmental mobility.…”
Section: Influence Of Maltose -Maltitol Mixtures On the β-Lg Matrixmentioning
confidence: 99%